Features of Development and Course of Disseminated Intravascular Coagulation Syndrome During Surgical Interventions in Children with Oncological Diseases - N. P. Leonov; V. V. Schukin; G. A. Novichkova; M. A. Maschan; F. I. Ataullakhanov; S. S. Yashin; A. M. Zeynalov; Е. A. Spiridonova (Общая реаниматология)
Coagulopathy always accompanies blood loss, and its transformation into disseminated intravascular coagulation syndrome (DIC) is associated with increased morbidity and mortality.Objective: to characterize the features of the development and course of DIC during bleeding, as well as identify the main predictors of its formation during surgical interventions in children with oncological diseases.Material and Methods. A retrospective study of children under 18 years of age with oncological pathology who received surgical treatment for the period from 2017 to 2019 years. Children who received blood transfusion and hemostatic therapy with intraoperative bleeding were selected. The resulting cohort (n=207) was divided into two groups using the modified ISTH assessment system: children with DIC (n=59), without DIC (n=148). Demographic, clinical, and laboratory factors were compared between groups. The final model of multivariate logistic regression included signs that were before the development of DIC on the second day after the operation and were selected as a result of univariate analysis (P<0.05), had less than 10% missing data and were clinically plausible. The prediction accuracy of the multivariate model was checked by analyzing the area under the ROC curve.Results. DIC was found to develop often in children with cancer during surgical operations in the retroperitoneal space (OR=2.09 [1.07; 4.05]; P=0.03) and liver (OR=3.86 [1.72; 8.67]; P=0.001). Multiple organ failure (MOF) was more severe and was represented by pulmonary, hepatic and renal failure in the group with identified DIC. The development of MOF was accompanied by a decrease in tissue perfusion and an increase in D-dimer. The probability of detecting acute thrombosis after surgery was 4.5 times higher in the group of patients with DIC than in the group without DIC (OR=4.5 [1.4; 14.3]; P=0.01). 90-daily survival was 84.41±6.49% [71.69%; 97.13%] in the group of patients with DIC, and 96.22±3.12 [90.1%; 100%] in the group without DIC. Multivariate analysis showed that age less than 8 years, platelet count less than 150X109/l, hypocalcemia less than 1 mmol/l and the period of intraoperative critical hypotension for more than 25 minutes are predictors of the development of DIC after surgery. ROC analysis showed excellent quality of the obtained predictive model (AUC=0,94 [0,9; 0,97]).Conclusion. In children with oncological diseases, in the presence of bleeding, coagulopathy in the postoperative period is transformed into a DIC-syndrome, proceeding clinically with the development of organ failure. Age less than 8 years, platelet count less than 150X109/l, hypocalcemia less than 1 mmol/L and a period of intraoperative critical hypotension of more than 25 minutes are predictors of the development of DIC. The extreme expression of the «organ» type DIC is the progression of thrombotic syndrome to life threatening complications, which reduces the 90-day survival by 12%.